Association between mother's access to health information and children under 12 years of age's access to oral health information in Peru, 2018 - Calampa, Geanny (2023)
Parents or the child's caregiver must have the required knowledge to prevent or limit the progression of pathologies that affect their children, including those related to oral health. Objective: To determine the association between mother's access to health information and children under 12 years of age's access to oral health information in Peru, 2018. Material and methods: The study was cross-sectional. The population consisted of 42 950 records of children under 12 years of age from the Demographic and Family Health Survey (ENDES) database, conducted in 2018, a single period. The final sample consisted of 27 910 records. The independent variable was the mother's access to health information, and the dependent variable was the access of children under 12 years of age in Peru to oral health information. Covariates included the area of residence, natural region, place of residence, health insurance, wealth quintile, age, and sex. The chi-square test at 95% CI, prevalence ratio (PR), and adjusted prevalence ratio (aPR) were used. Results: No association was found between access to maternal health information and access of children under 12 years of age to oral health information (PR = 0.99; 95 % CI: 0.965-1.02); there is also no association when considering the covariates (region, place of residence, wealth quintile and age), aPR = 1.00 (95 % CI: 0.96-1.03). Conclusion: No association between mother's access to health information and access of children under 12 years of age in Peru to oral health information during 2018.